The Society's Participation of Partner Polhut at Effort of Protection and Forest Security at Way Kambas National Park - Sukarman Sukarman (Department of Forestry, Faculty of Agriculture, University of Lampung, 2018)
Protection and forest security base on the local society participation represent an effort to take care of to protecting and maintaining forest trouble loss. Management of Way Kambas National Park (TNWK) less be effective considering the broadness of forest area managed and the number of trouble problems to forest area. Society Partner of forest police (MMP) is society group about assistive forest police (Polhut) in execution of forest protection under coordination, construction and observation of instution builder. Objective of this research is to learn the storey level participation and factors which deal with participation MMP protection and forest security. Method of data intake use the method of census and survei. Population only amount to 64 people so that altogether taken as sampel. Analysed data with the correlation test. Age, education, old join at group, work tipe, conditions equipment, conditions equipment and maintenance have not relation which significan and education, work tipe, condition equipment and conditions equipment and maintenance have negative corelations with the participation of group MMP on protection and forest security in TNWK. Keyword: group of community, forest protection, participate.